Investigating Security Challenges in Primary Schools Student Enrolment within Frontline Local Governments with Security Threats in Katsina State - Bello, Ashiru; Abubakar, Salisu Bala (Sahel Journal of Life Sciences FUDMA, 2024)
This study investigated the impact of security challenges on primary school enrolment in frontline local government areas (LGAs) of Katsina State, including Jibia, Batsari, Safana, Danmusa, and Dutsin-Ma. A descriptive survey design was employed, utilizing qualitative methods to collect and analyze data. Enrolment records from selected schools over three years were examined using percentage analysis to identify trends and patterns. Observations of school security measures further contextualized the findings. Data were presented using visual tools such as tables. Ethical considerations were prioritized, including informed consent, confidentiality, and voluntary participation. A significant decline in school attendance has been observed across these LGAs, with enrolment rates dropping drastically from 2022 to 2024. The study revealed a significant enrolment trend linked to security challenges, highlighted parental safety concerns and provided actionable recommendations to improve access to education in vulnerable areas.